Teaching presentation skills in English language classes - Elvira E. Valleva; Marina O. Polukhina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
In the modern world, public speaking skills are an important component of the education of future engineers and scientists. The lack of specific disciplines aimed at the formation of presentation skills means that most university graduates are unprepared to present at scientific conferences and professional meetings. Therefore, the discipline "Foreign Language", which includes the development of communicative speech skills, can be used for these purposes. This paper presents the experience of teaching presentation skills in English language classes to Master’s degree students majoring in engineering at the Department of Foreign Languages for Professional Communication at Kazan National Research Technological University. A large number of scientific and methodological works published on this topic make it possible to determine the stages and educational material for teaching presentation skills in a foreign language. The authors propose the technique for the gradual formation of skills in planning, designing and presenting the main parts of academic presentations in the English Language. The teaching materials and exercises presented here have been based on existing well-known practices and meet the international standards for presentation skills.